In vivo measurement of ethanol metabolism in the rat liver using magnetic resonance spectroscopy of hyperpolarized [1-(13)C]pyruvate - Spielman, Daniel M. (2009)
[1-13C]pyruvate is readily polarizable substrate that has been the subject of numerous magnetic resonance spectroscopy (MRS) studies of in vivo metabolism. In this work, (13)C-MRS of hyperpolarized [1-(13)C]pyruvate is used to interrogate a metabolic pathway involved in neither aerobic nor anaerobic metabolism. In particular, ethanol consumption leads to altered liver metabolism, which when excessive is associated with adverse medical conditions including fatty liver disease, hepatitis, cirrhosis, and cancer. Here we present a method for noninvasively monitoring this important process in vivo. Following the bolus injection of hyperpolarized [1-(13)C]pyruvate, we demonstrate a significantly increased rat liver lactate production rate with the co-administration of ethanol (P = 0.0016 unpaired t-test). The affect is attributable to increased liver nicotinamide adenine dinucleotide (NADH) associated with ethanol metabolism in combination with NADH's role as a coenzyme in pyruvate to lactate conversion. Beyond studies of liver metabolism, this novel in vivo assay of changes in NADH levels makes hyperpolarized [1-(13)C]pyruvate a potentially viable substrate for studying the multiple in vivo metabolic pathways that use NADH (or NAD(+)) as a coenzyme, thus broadening the range of applications that have been discussed in the literature to date.